2012
DOI: 10.1002/aic.13781
|View full text |Cite
|
Sign up to set email alerts
|

PVAm–PIP/PS Composite Membrane with High Performance for CO2/N2 Separation

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Polyvinylamine (PVAm) was modified using a cross-linking agent containing carriers piperazine (PIP). Attenuated total reflectance fourier transform infrared, elemental analyzer, and X-ray diffraction were used to characterize the PIP-modified PVAm. The PVAm-PIP/polysulfone (PS) composite membrane was developed by coating PVAm-PIP mixed solutions with different mass ratios of PIP/PVAm (m PIP /m PVAm ) on the PS ultrafiltration membrane. The effects of m PIP /m PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
183
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 314 publications
(189 citation statements)
references
References 46 publications
6
183
0
Order By: Relevance
“…2 [14,24]. It has been deduced that the intermolecular hydrogen bonds in the PVAm-PIP film formed between the secondary amine group of PIP and the primary amine group in PVAm [24], and the intermolecular hydrogen bonds in the PVAm-EDA film formed between primary amine group of EDA and the amide group or primary amine group in PVAm [14].…”
Section: Characterization Of the Filmsmentioning
confidence: 97%
See 1 more Smart Citation
“…2 [14,24]. It has been deduced that the intermolecular hydrogen bonds in the PVAm-PIP film formed between the secondary amine group of PIP and the primary amine group in PVAm [24], and the intermolecular hydrogen bonds in the PVAm-EDA film formed between primary amine group of EDA and the amide group or primary amine group in PVAm [14].…”
Section: Characterization Of the Filmsmentioning
confidence: 97%
“…2 [14,24]. It has been deduced that the intermolecular hydrogen bonds in the PVAm-PIP film formed between the secondary amine group of PIP and the primary amine group in PVAm [24], and the intermolecular hydrogen bonds in the PVAm-EDA film formed between primary amine group of EDA and the amide group or primary amine group in PVAm [14]. Moreover, based on the literature [14], the XPS analyses of the PVAm-EDA/PS membrane also indicated that the intermolecular hydrogen bonds in the PVAm-EDA/PS membrane formed between the primary amine groups of EDA and the amide groups in PVAm.…”
Section: Characterization Of the Filmsmentioning
confidence: 99%
“…Mixed-gas separation of CO 2 with the AMT/PSf membrane compared with that of RMT/PSf and other polymeric and mixed-matrix membranes reported in the literature, tested using dry gases. [13][14][15][16][17][18][19][20][21] Ü Ü These are not the final page numbers! a much higher CO 2 /H 2 separation performance in particular (see the Supporting Information).…”
mentioning
confidence: 99%
“…These contaminants could possibly affect the performance of facilitated transport membranes via degrading carriers, competitive sorption with CO 2 or competitive reaction with CO 2 . Therefore, effects of various potential impurities on facilitated transport membranes containing amino groups and carbonate groups have been widely investigated by several research groups [284,291,[305][306][307][308]. According to these studies, there was a negative effect of minor contaminants on membrane performances observed.…”
Section: Facilitated Transport Membranesmentioning
confidence: 99%
“…In recent years, our group introduced a novel method that various amino group-containing small molecules were used to modify amino group-rich polymers via hydrogen-bonding crosslinking, which not only could achieve the optimization of membrane material structures at multiple levels, but also could increase the carrier concentration in the membranes [283][284][285][286][287]. Following this strategy, ethylenediamine (EDA), piperazine (PIP), monoethanolamine (MEA) and methylcarbamate (MC) were used as modifiers to incorporate into the PVAm matrix, and the formed hydrogen-bonding crosslinked networks were illustrated in Fig.…”
Section: Facilitated Transport Membranesmentioning
confidence: 99%